2016
DOI: 10.3390/ijerph13030314
|View full text |Cite
|
Sign up to set email alerts
|

A Cross Section Study to Determine the Prevalence of Antibodies against HIV Infection among Hepatitis B and C Infected Individuals

Abstract: (1) Background: There are limited data regarding human immunodeficiency virus (HIV) prevalence among hepatitis B virus (HBV) or hepatitis C virus (HCV) infected individuals. The aim of this cross-sectional study is to determine the prevalence of HBV and HCV infection among HIV individuals; (2) Methods: A total of 409 patients (126 HBV+ and 283 HCV+) referred to the Brazilian Reference Laboratory for Viral Hepatitis from 2010 to 2013 donated serum samples. Anti-HIV, HBsAg, anti-HBc, anti-HBs, anti-HBcIgM, anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
17
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 35 publications
8
17
2
1
Order By: Relevance
“…Recent studies found anti-HCV prevalence in HIV infected individuals of 1.3% in Northeast Brazil, 4.6% in Southeast Brazil, 12.9% in South Brazil, 6.9-9.7% in Midwest Brazil [16,17,[24][25][26]. In all of these studies, HCV genotype 1 was the most prevalent.…”
Section: Hepatitis B and C Prevalence In Patients Infected By Hivmentioning
confidence: 94%
See 1 more Smart Citation
“…Recent studies found anti-HCV prevalence in HIV infected individuals of 1.3% in Northeast Brazil, 4.6% in Southeast Brazil, 12.9% in South Brazil, 6.9-9.7% in Midwest Brazil [16,17,[24][25][26]. In all of these studies, HCV genotype 1 was the most prevalent.…”
Section: Hepatitis B and C Prevalence In Patients Infected By Hivmentioning
confidence: 94%
“…In Brazil, HBsAg prevalence in HIV infected individuals ranges from 1.9 to 10.3% according geographical regions [15][16][17][18]. Tengan et al [15] reported HBsAg prevalence in HIV of 3.3% in [20,21].…”
Section: Hepatitis B and C Prevalence In Patients Infected By Hivmentioning
confidence: 99%
“…Since HIV and HBV present similar modes of transmission, coinfection has been reported . In this context, it is important to identify those HIV‐infected individuals who are susceptible to HBV infection through detecting anti‐HBs and to recommend HBV vaccination to those who do not present anti‐HBs.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] Since HIV and HBV present similar modes of transmission, coinfection has been reported. 16,17 In this context, it is important to identify those HIV-infected individuals who are susceptible to HBV infection through detecting anti-HBs and to recommend HBV vaccination to those who do not present anti-HBs. In low resource areas, it is very difficult to collect, transport, and test serum samples, making DBS assays a powerful tool in increasing access to diagnostic testing.…”
mentioning
confidence: 99%
“…Human immunodeficiency virus (HIV) and hepatitis C virus (HCV) share the parenteral route as a mode of transmission . In the general population, a low prevalence of HCV infection was found (less than 1%), but a high prevalence of HIV/HCV coinfection is observed worldwide, especially in areas where intravenous drug use is the main route of transmission …”
Section: Introductionmentioning
confidence: 99%